Should Spinal Anesthesia Be Used for Spine Surgery: A Case Report - Gabrielle A. White-Dzuro; Xiaodong Bao; Francis McGovern; Robert A. Peterfreund (Case Reports in Anesthesiology)
A patient with lumbar spine stenosis presented for lumbar spine decompression, clearly stating a preference for spinal anesthesia (SA) over general anesthesia (GA). Surgery was performed under uneventful SA without sedation. The patient recovered from surgery quickly and without incident, requiring no postoperative opioid analgesia. What data support administering SA for lumbar spine surgery? A literature search found nine recently published reviews favoring SA over GA. These reviews cited many of the same, older, flawed, primary research reports. Although choosing SA was reasonable, our literature analysis suggests blind reliance on summary conclusions of reviews and meta-analyses may be misleading.